Optimal Operation of Autonomous Energy System Based on Multi-objective Approach - Paul Rodrigues; Ashish Singh; Vikas Kaushik; Jasgurpreet Singh Chohan; Mustafa Adnan Abdulrahman; Layth Hussein; Huamán-Romaní, Yersi-Luis (International Journal of Integrated Engineering, 2024)
The present investigation on the optimal scheduling of the autonomous energy system (AES) considers technical and economic indices. Demand management has been proposed to enhance the technical and economic indices during operation. The implementation of load demand management is contingent upon bid prices offered to consumers for the purpose of reducing demand during emergency situations. The economic and technical objectives are based on multi-objective modeling, which includes minimizing operational costs and improving voltage indices. The optimization of the multi-objective problem is executed through the utilization of the Particle swarm optimization (PSO) algorithm. The desired optimal solution within the non-dominated solutions is obtained by employing the fuzzy max-min method. Ultimately, to demonstrate the efficacy and validation of the proposed strategy, the aforementioned strategy is implemented in two case studies on the 33 bus IEEE test system.